The impact of coronavirus on China’s SMEs: Findings from the enterprise survey for innovation and entrepreneurship in China - Dai, Ruochen; Hu, Junpeng; Zhang, Xiaobo (Center for Global Development, 2020)
Since the coronavirus outbreak began in January, Chinese business activity has been severely slowed, affecting China’s position in the global industrial supply chain. The Enterprise Survey for Innovation and Entrepreneurship in China (ESIEC) launched a survey on the “condition of micro, small and medium-sized enterprises (SMEs) amidst the coronavirus outbreak.” Our surveyors then conducted follow-up interviews with a representative sample of private entrepreneurs from a database maintained over the past three years, asking about the resumption of production as well the different challenges enterprises face.